Ascertaining social worker contacts in routine mental healthcare and describing their distribution: a descriptive analysis of electronic records data from a large south London mental healthcare provider - Robert Stewart; Amelia Jewell; Gayan Perera; Norah Alothman (BMJ Open)
Objectives To describe the distribution of contacts with mental health service-employed social workers over time and by patient characteristics using routine mental health service data resources.Design A descriptive study.Setting and participants In a large secondary mental healthcare provider in London serving a geographic catchment of around 1.3 million residents, mental health social worker contacts were ascertained from the case note entries for all patients aged 16 years or above at the time of contact who received treatment in any services from 2008 to 2023.Main outcome measures Patient demographic and clinical characteristics at or closest to the social worker contact event.Results A total 1 541 078 social worker contacts were extracted. Contacts were most likely in the 20–39 years age group (38.1%), in men (51.9%), in patients from white (45.3%) and black (38.8%) ethnic groups, in those who were non-cohabiting (89.9%) and in those living in more deprived neighbourhoods. The most likely diagnosis in those receiving social work contacts was schizophrenia (39.2%). Males had the highest number of face-to-face social worker contacts, and females were more represented in phone and video contacts. Over the past 16 years, social worker contacts were highest between 2014 and 2015.Conclusions To the best of our knowledge, this study is the first quantification of social work deployment within mental healthcare. Research into the role of social workers within mental health services has been of small scale and predominantly qualitative to date. However, growing data resources, building on distributions of service provision, present important opportunities for wider evaluation of the role of this professional group and the interventions they support within multidisciplinary teams.